Advances and gaps in studies on healthy meat products and their relationship with regulations: The Brazilian scenario - Rios-Mera, Juan D. (2021)
Juan D. Rios-Mera thanks the support of the Consejo Nacional de Ciencia, Tecnología e Innovacion ´ Tecnologica ´ - CONCYTEC from Peru (CIENCIACTIVA programme, PhD scholarship contract: No. 238-2018- FONDECYT).